2021
DOI: 10.1021/acs.inorgchem.1c01161
|View full text |Cite
|
Sign up to set email alerts
|

Argentivorous Molecules with Chromophores in Side Arms: Silver Ion-Induced Turn On and Turn Off of Fluorescence

Abstract: The synthesis of argentivorous molecules (L1 and L2 ) having two chromophores (4-(anthracen-9-yl)­benzyl or 4-(pyren-1-yl)­benzyl groups) and two benzyl groups and the fluorescence properties of their silver complexes in a solution and the solid state are reported. A crystallographic approach for the Ag+ complexes with L1 and L2 revealed that the observed fluorescence changes stem from the excimer formation and extinction of fluorescent. Furthermore, binding stabilities of L1 and L2 toward Ag+ ions were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Maier et al reported that the strength of the intermolecular Ag + –π interaction in solution was −1.34 to −2.63 kcal/mol . In addition, the structures of tetra-armed cyclen/Ag + complexes in the data previously reported showed only two types of conformers: Δ­( δδδδ ) and Λ­( λλλλ ) forms. ,,,, Therefore, we performed DFT calculations (B3LYP/6-31G*) of the Λ­( λλλλ ) form and its side arm rotated isomer, Δ­( λλλλ ) form, to investigate whether the silver­(I) complex with 1,4,7,10-tetrabenzyl-1,4,7,10-tetraazacyclododecane forms not only stable Δ­( δδδδ ) and Λ­( λλλλ ) but also Δ­( λλλλ ) and Λ­( δδδδ ) forms (Figure S17). As a result, the energy difference between Λ­( λλλλ ) and Δ­( λλλλ ) forms was about 8.6 kJ/mol, and the relative amounts of each isomer would be 2.1 × 10 6 :1 (=Λ­( λλλλ ):Δ­( λλλλ )) (Table S1).…”
Section: Resultsmentioning
confidence: 93%
“…Maier et al reported that the strength of the intermolecular Ag + –π interaction in solution was −1.34 to −2.63 kcal/mol . In addition, the structures of tetra-armed cyclen/Ag + complexes in the data previously reported showed only two types of conformers: Δ­( δδδδ ) and Λ­( λλλλ ) forms. ,,,, Therefore, we performed DFT calculations (B3LYP/6-31G*) of the Λ­( λλλλ ) form and its side arm rotated isomer, Δ­( λλλλ ) form, to investigate whether the silver­(I) complex with 1,4,7,10-tetrabenzyl-1,4,7,10-tetraazacyclododecane forms not only stable Δ­( δδδδ ) and Λ­( λλλλ ) but also Δ­( λλλλ ) and Λ­( δδδδ ) forms (Figure S17). As a result, the energy difference between Λ­( λλλλ ) and Δ­( λλλλ ) forms was about 8.6 kJ/mol, and the relative amounts of each isomer would be 2.1 × 10 6 :1 (=Λ­( λλλλ ):Δ­( λλλλ )) (Table S1).…”
Section: Resultsmentioning
confidence: 93%
“…Synthesis of new tetra-armed cyclens with anthracene units (L 2 and L 3 ) Tetra-armed cyclens (L 2 and L 3 , Fig. 1) were prepared by reductive amination of 1,7-dibenzyl-1,4,7,10-tetraazacyclododecane (1, 1,7-dibenzylcyclen) 25 with the corresponding anthracenyl benzaldehydes (5 and 6) in the presence of NaBH(OAc) 3 . 9-Bromomethylanthracene (2) 26 and 2-(anthracen-9-yl)ethyl-4methyl benzenesulfonate (3) 27 were prepared according to the procedure described in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that the resonance is inhibited by the orthogonality between the phenyl group and anthracene, as shown by the X-ray crystallographic analysis reported previously. 25…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations